"Immigration Enforcement Is a Daily Part of Our Students' Lives": School Social Workers' Perceptions of Racialized Nested Contexts of Reception for Immigrant Students - Sophia Rodriguez; Benjamin J. Roth; Leticia Villarreal Sosa (SAGE Publishing, 2022)
This qualitative analysis examines school social workers' equity work for immigrant students, including their perceptions of immigration enforcement and school climates that support or hinder immigrant student experiences. We conceptually expand understandings of nested contexts of reception and racialized organizations across macro, meso, micro levels, and how they affect immigrant students' educational experiences, mobility, and belonging. Utilizing open-ended responses from a unique national survey data set, we examine school social workers' perceptions of the macro, meso, micro racialized contexts that immigrant students encounter, how school social worker perceptions reflect racial attitudes as part of the racialized organization of schools in which they work, and how such racial attitudes influence their actions and potentially disrupt racial inequality in schools. Discussion of the impact of school social workers' racial attitudes, and perceptions of racialized contexts and how they influence school social workers' advocacy for immigrant students is offered.